2019
DOI: 10.1021/acscentsci.9b00843
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of Hydrophobicity in Amphiphilic Polyaspartamide Derivatives for Rapid and Transient Expression of Messenger RNA Directed Toward Genome Engineering in Brain

Abstract: Rapid and transient expression of in vitro transcribed mRNA (IVT mRNA) in target cells is a current major challenge in genome engineering therapy. To improve mRNA delivery efficiency, a series of amphiphilic polyaspartamide derivatives were synthesized to contain various hydrophobic moieties with cationic diethylenetriamine (DET) moieties in the side chain and systematically compared as mRNA delivery vehicles (or mRNA-loaded polyplexes). The obtained results demonstrated that the side chain structures of polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…Poly(aspartamide)s conjugated to ionizable aminoethylene side chains are protonated at the acidic pH inside endosomes, facilitating RNA delivery. The hydrophobicity and length of the side chain influence poly(aspartamide) protonation and delivery efficacy 93 . For example, PEGylated poly(aspartamide) with an ethylenediamine side chain delivers mRNA to liver 94 , brain 95 , spinal cord 96 , knee joint 97 and olfactory nerves 98 .…”
Section: Delivery Vehicles For Mrna Vaccinesmentioning
confidence: 99%
“…Poly(aspartamide)s conjugated to ionizable aminoethylene side chains are protonated at the acidic pH inside endosomes, facilitating RNA delivery. The hydrophobicity and length of the side chain influence poly(aspartamide) protonation and delivery efficacy 93 . For example, PEGylated poly(aspartamide) with an ethylenediamine side chain delivers mRNA to liver 94 , brain 95 , spinal cord 96 , knee joint 97 and olfactory nerves 98 .…”
Section: Delivery Vehicles For Mrna Vaccinesmentioning
confidence: 99%
“…[ 12,13 ] The cation‐π interactions between the side chains of arginine and tryptophan, tyrosine, or phenylalanine play an important role in these processes. [ 14,15 ] Considering the hydrophobic nature of the π‐faces in guanidinium ions, such stacking against hydrophobic side chain in a protein could reduce the entropic cost of hydrophobic hydration. Jobin et al.…”
Section: Methodsmentioning
confidence: 99%
“…Mice pre-treatment with NEP mRNA micelles increased NEP concentration and almost doubled its proteolytic activity in brain and diminished almost to half the amount of exogenous Aβ 1-40 injected thereafter as compared to other groups. The authors recently reported an upgrade of these polypeptide nanocarriers by fine-tuning the hydrophobicity (logP) of the P(Asp) residues in the side chains [271]. A direct correlation among logP and polyplex stability and cell internalisation efficiency was found.…”
Section: Localised Deliverymentioning
confidence: 99%